(untitled) (Journal of Enam Medical College, 2025)
Background: CA 125, as a biomarker, holds promise in a wide range of applications, including risk assessment, early detection, diagnosis, prognosis, monitoring, and therapy. Objectives: To find out expression of AgNOR staining in benign, borderline and malignant epithelial tumors of ovary and its correlation with serum CA 125. Materials and Methods: The cross-sectional analytical study, spanning from March 2018 to July 2020 in the Department of Pathology, Sir Salimullah Medical College, Dhaka included 70 diagnosed cases of ovarian epithelial tumors with known CA 125 status. Paraffin blocks and CA 125 reports were gathered, ensuring ethical practices throughout. Results: The mean CA 125 levels in patients with benign was 61.70±30.75 U/mL, in borderline group 65.0±7.07 U/mL and in malignant cases 463.67±249.48 U/mL. CA 125 level was significantly higher in malignant tumors compared to benign and borderline (p<0.001). There was significant positive correlation between CA 125 with mAgNOR (r=0.821; p=0.001) and with pAgNOR (r=0.853; p=0.001). Conclusion: Elevated CA 125 levels were notably significant in malignant tumors compared to benign and borderline cases. A strong, positive correlation existed between CA 125 and both mAgNOR and pAgNOR. J Enam Med Col 2022; 12(3): 137−142